Linguistic Change and Language Contact. New perspectives and interpretations on Spanish in South America and Chile - Olate Vinet, Aldo; Becerra Parra, Rodrigo; Alonqueo Boudon, Paula (Lenguas Modernas, 2011)
This paper discusses the theoretical problem of linguistic change from a language contact approach. In this context, we present the main theoretical contributions made by different authors who at first rejected an a priori rigid conceptualization of language change and have tried, more recently, to account for linguistic change from a multidimensional approach based on functionalist and cognitive perspectives. In this respect, Lenz’s hypothesis is revisited 100 years later in the light of the renewal of the theoretical and disciplinary frameworks developed over the last 30 years. We focus particularly on the discussion of contact-induced change of Spanish in Latin America and criticize the hegemonic and stigmatizing Hispanist perspective that has prevailed in the studies of Spanish in America. Finally, we propose a theoretical and methodological approach to study Spanish in Mapuche-contact areas in which we put forward the possibility of grammatical transfers from Mapuche to Spanish.